2015
DOI: 10.1016/j.nmni.2015.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

First detection of Aspergillus fumigatus azole-resistant strain due to Cyp51A TR46/Y121F/T289A in an azole-naive patient in Spain

Abstract: We report the first isolation of a voriconazole-resistant Aspergillus fumigatus strain harbouring the azole resistance mechanism TR46/Y121F/T289A, recovered from an azole-naive patient in Spain with chronic obstructive pulmonary disease. This new finding in Spain suggests the spread of this resistance mechanism and reinforces the need for antifungal susceptibility surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 10 publications
4
15
0
1
Order By: Relevance
“…Despite previous studies in Spain showing low rates of A. fumigatus azole resistance (19,21,28), resistance to at least one azole was found in 23 strains molecularly identified as A. fumigatus sensu stricto Three strains had the most frequent mechanism of azole resistance described worldwide (TR 34 /L98H) (29)(30)(31) and one TR 46 /Y121F/T289A mechanism (32). These two resistance-related changes have been previously described in Spanish isolates (19,33,34), TR 34 /L98H is associated with a panazole resistance profile, and TR 46 /Y121F/T289A is related to voriconazole and isavuconazole resistance and variable MICs for itraconazole and posaconazole (35,36), although the isolate carrying it in this study was resistant to all azoles. Two other A. fumigatus strains harbored a substitution of glycine for arginine at position 54 of cyp51A, which has been linked to cross-resistance to itraconazole and posaconazole (37,38), in agreement with the MICs obtained in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Despite previous studies in Spain showing low rates of A. fumigatus azole resistance (19,21,28), resistance to at least one azole was found in 23 strains molecularly identified as A. fumigatus sensu stricto Three strains had the most frequent mechanism of azole resistance described worldwide (TR 34 /L98H) (29)(30)(31) and one TR 46 /Y121F/T289A mechanism (32). These two resistance-related changes have been previously described in Spanish isolates (19,33,34), TR 34 /L98H is associated with a panazole resistance profile, and TR 46 /Y121F/T289A is related to voriconazole and isavuconazole resistance and variable MICs for itraconazole and posaconazole (35,36), although the isolate carrying it in this study was resistant to all azoles. Two other A. fumigatus strains harbored a substitution of glycine for arginine at position 54 of cyp51A, which has been linked to cross-resistance to itraconazole and posaconazole (37,38), in agreement with the MICs obtained in this study.…”
Section: Discussionsupporting
confidence: 75%
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, other promoter mutations (TR 46 ) and amino acid substitutions (Y121F and T289A) may change the shape of the binding channels to confer resistance to commonly used antifungal drugs (Snelders et al 2010(Snelders et al , 2015. These mutations have also been associated with resistant isolates from patients in the United States (Wiederhold et al 2016), Spain (Peláez et al 2015), Japan (Hagiwara et al 2016), Iran (Seyedmousavi et al 2013), Turkey (Özmerdiven et al 2015), and Taiwan (Wu et al 2015). Likewise, these mutations were related to environmental isolates from flower fields in Colombia (Alvarez-Moreno et al 2017), greenhouses for vegetables and fruits in China (Ren et al 2017), and potato and fenugreek fields in India (Chowdhary et al 2014) that were all treated with fungicides.…”
Section: Treatment Options: Antifungal Drugs and Mechanisms Of Resistmentioning
confidence: 99%